Prospective validation of a new imaging scorecard to assess leptomeningeal metastasis: a joint EORTC BTG and RANO effort - Le Rhun, Emilie; Devos, Patrick; Winklhofer, Sebastian; Lmalem, Hafida; Brandsma, Dieta; Kumthekar, Priya; Castellano, Antonella; Compter, Annette; Dhermain, Frederic; Franceschi, Enrico; Forsyth, Peter; Furtner, Julia; et al. (Neuro-Oncology, 2022)
Validation of the 2016 RANO MRI scorecard for leptomeningeal metastasis failed for multiple reasons. Accordingly, this joint EORTC Brain Tumor Group and RANO effort sought to prospectively validate a revised MRI scorecard for response assessment in leptomeningeal metastasis.Coded paired cerebrospinal MRI of 20 patients with leptomeningeal metastases from solid cancers at baseline and follow-up after treatment and instructions for assessment were provided via the EORTC imaging platform. The Kappa coefficient was used to evaluate the interobserver pairwise agreement.Thirty-five raters participated, including 9 neuroradiologists, 17 neurologists, 4 radiation oncologists, 3 neurosurgeons, and 2 medical oncologists. Among single leptomeningeal metastases-related imaging findings at baseline, the best median concordance was noted for hydrocephalus (Kappa = 0.63), and the worst median concordance for spinal linear enhancing disease (Kappa = 0.46). The median concordance of raters for the overall response assessment was moderate (Kappa = 0.44). Notably, the interobserver agreement for the presence of parenchymal brain metastases at baseline was fair (Kappa = 0.29) and virtually absent for their response to treatment. 394 of 700 ratings (20 patients x 35 raters, 56%) were fully completed. In 308 of 394 fully completed ratings (78%), the overall response assessment perfectly matched the summary interpretation of the single ratings as proposed in the scorecard instructions.This study confirms the principle utility of the new scorecard, but also indicates the need for training of MRI assessment with a dedicated reviewer panel in clinical trials. Electronic case report forms with “blocking options” may be required to enforce completeness and quality of scoring.
Gesehen am 29.11.2022